1993
DOI: 10.1002/art.1780360103
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity before disease onset in women with rheumatoid arthritis

Abstract: Objective. To examine fecundity prior to disease onset in women with rheumatoid arthritis (RA).Methods. Two hundred fifty-nine RA patients with an opportunity for pregnancy were compared with 1,258 control women as part of a prospective cas+ control study of recent-onset RA in women.Results. A 12-month or longer interval to pregnancy was found in 42% of RA cases compared with 34% of controls (odds ratio = 1.44, 95% confidence interval 1.10, 1.91). This difference was not accounted for by an older age when atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 14 publications
4
35
1
3
Order By: Relevance
“…In addition, women diagnosed with RA before age 18 years or before bearing children were found to have fewer total children than women diagnosed later in their lives (3,4,11). Other studies detected no differences in conception rates, but these were early investigations that did not distinguish between a woman's intention to conceive and her ability to conceive (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women diagnosed with RA before age 18 years or before bearing children were found to have fewer total children than women diagnosed later in their lives (3,4,11). Other studies detected no differences in conception rates, but these were early investigations that did not distinguish between a woman's intention to conceive and her ability to conceive (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…RA probably does not affect fertility, although a decrease in fecundity prior to disease onset (time interval to conception) has been described. (Nelson et al 1993a) There is no evidence that RA increases risk of spontaneous abortions, preterm labor or preeclampsia. (Branch and Porter 1999;Nelson and Ostensen 1997) Plasma cortisol, which rises during pregnancy to peak at term, was initially thought to be important in the pregnancy-induced amelioration of RA.…”
Section: A Rheumatoid Arthritis and The Changing Maternal "Self" Hypmentioning
confidence: 99%
“…Two other studies have suggested that fertility or fecundity may be decreased among women with RA (116,117), whereas others have found that fertility or fecundity do not differ from healthy controls (112). Although fertility is normal in SLE, increased fetal loss either as miscarriage or stillbirth has been reported (118 -122).…”
Section: Systemic Diseases and Ovarian Dysfunctionmentioning
confidence: 99%